2008
DOI: 10.1177/0269881108094650
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of serotonin-1A receptor function in the human psychopharmacology of MDMA

Abstract: Serotonin (5-HT) release is the primary pharmacological mechanism of 3,4-methylenedioxymethamphetamine (MDMA, 'ecstasy') action in the primate brain. Dopamine release and direct stimulation of dopamine D2 and serotonin 5-HT2A receptors also contributes to the overall action of MDMA. The role of 5-HT1A receptors in the human psychopharmacology of MDMA, however, has not yet been elucidated. In order to reveal the consequences of manipulation at the 5-HT1A receptor system on cognitive and subjective effects of MD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
35
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 56 publications
8
35
0
Order By: Relevance
“…These data suggest that 5-HT 1A receptors do not have a crucial role in the neuropharmacology of MDMAinduced memory impairment. These finding confirm recent results from a study assessing the role of 5-HT 1A receptors on MDMA effects on visual-spatial working memory as measured with a CANTAB test battery (Hasler et al, 2009) in a placebo-controlled study. A single dose of MDMA significantly impaired visual-spatial memory as compared with placebo.…”
Section: Discussionsupporting
confidence: 89%
“…These data suggest that 5-HT 1A receptors do not have a crucial role in the neuropharmacology of MDMAinduced memory impairment. These finding confirm recent results from a study assessing the role of 5-HT 1A receptors on MDMA effects on visual-spatial working memory as measured with a CANTAB test battery (Hasler et al, 2009) in a placebo-controlled study. A single dose of MDMA significantly impaired visual-spatial memory as compared with placebo.…”
Section: Discussionsupporting
confidence: 89%
“…Apart from sporadic use of cannabis, one subject reported a single previous experience with a hallucinogenic drug (psilocybin), two subjects had previously used both MDMA and a hallucinogen, and seven subjects were drug-naïve. Subjective (primary outcome) and neurocognitive results from the present study have previously been reported 10. Here we present the previously unpublished cardiovascular and adverse effects (secondary outcomes) of the same study subjects10 with one additional subject.…”
Section: Methodssupporting
confidence: 56%
“…Subjective (primary outcome) and neurocognitive results from the present study have previously been reported 10. Here we present the previously unpublished cardiovascular and adverse effects (secondary outcomes) of the same study subjects10 with one additional subject.…”
Section: Methodssupporting
confidence: 56%
See 1 more Smart Citation
“…An involvement of 5-HT 1A Rs in the action of MDMA has not been clearly established. In human volunteers, there were only limited effects of pretreatment with the 5-HT 1A R antagonist, pindolol, on the MDMA-induced changes in sustained attention and visual-spatial memory (Hasler et al 2009), while in rats, MDMA-induced locomotor hyperactivity was modulated only to a minor extent by pre-treatment with the 5-HT 1A R antagonist, WAY 100, 635 (McCreary et al 1999). On the other hand, acute facilitation of social interaction by MDMA in rats was prevented by pre-treatment with WAY 100,635, but not by a 5-HT 1B R or 5-HT 2A R antagonist (Morley et al 2005).…”
Section: Discussionmentioning
confidence: 99%